Description of Adolescent Compliance to the Implementation of 3M During the Covid-19 Pandemic - Nadya Yulistiana; Qurrotul Aeni; Andriyani Mustika Nurwijayanti (Global Health Science Group, 2022)
The Covid-19 Pandemic period is very influential on adolescent compliance, because they are required to apply the 3M health protocol, whether you like it or not, you have to keep doing it because it is to prevent the spread of Covid-19. The aim is to determine community compliance with the application of 3M (Washing hands, Wearing masks, Maintaining distance) during the Covid-19 Pandemic in the East Tapak Hamlet, Kedunggading Village. The design of this research is descriptive with a survey approach. The sample in this study amounted to 68 respondents with a purposive sampling technique. The measuring instrument used is a compliance questionnaire. The results of this study indicate that the average age is 19 years with the youngest 13 years old and the oldest 24 years old, the majority of respondents are female and most of the respondents have high school education. Adolescents' compliance with the application of health protocols is very good because they always wash their hands before and after doing activities, use masks when going out of the house/public places, and always keep a distance of 1 meter from other people. Adolescents need to increase compliance with the application of obedient 3M to be very obedient in order to reduce the transmission rate of Covid-19